Experimental Study on a Low-Rise Shear Wall with the Built-In Shear Steel Plate - Xingyu Song; Lin Zhao; Lingkun Chen; Yuan Duan; Yehao Jiang; Yuan Tian (Advances in Civil Engineering)
In this paper, a new reinforcement scheme is proposed to improve the seismic performance of low-rise shear walls. The new system combines the advantages of slotted and composite shear walls to exhibit a high bearing capacity and good deformation performance. Two low-cycle repeated loading tests with different forms of shear walls were conducted to accurately understand its seismic performance. Seismic performance indexes, such as failure mode, bearing capacity, hysteresis curve, stiffness degradation, and energy dissipation capacity, of the new shear wall under the low-cycle reciprocating load were obtained to verify its reliability. The results show that the newly reinforced shear wall has two clear seismic defense lines. Its deformation and energy-dissipation capacities and lateral stiffness stability are greatly improved compared with traditional low-rise shear walls. Thus, the proposed method can provide a new means for enhancing the seismic performance of shear walls.